Effect of Combined Regulatory Behavior Index (CRBI) on regulatory fatigue and behavioral adaptability (classical and reformulated) in the university context - de la Fuente, Jesús; Ubani, Ena; Karagiannopoulou, Evangelia; Kauffman, Douglas F. (Frontiers in Psychology, 2025)
IntroductionRegulatory fatigue is a potential explanatory mechanism for dysfunctional regulatory behavior, which would lead to poorly adaptive behavior. Based on this premise, it was hypothesized that it would have a significant mediating effect between the combined regulation level (average internal-external regulation) and the students' adaptability.MethodA total of 365 undergraduates completed, at three points in time, two standardized inventories during a 4-month period. Under an ex post-facto design, linear, inferential and mediational analyses were carried out to verify these effects.ResultsThe results showed that the combined regulation level was a significant predictor of fatigue and adaptability, as well as fatigue with respect to adaptability. This effect was corroborated at the inferential level. The most significant model showed the mediational value of fatigue between both, the regulation level, and adaptability, with special significance for the reformulated adaptability.DiscussionThe implications and limitations of the work are discussed. The relevant role of the combined level of regulation (personal and contextual) is noted, and above all, the relevance of regulatory fatigue as a mechanism that encourages the transition from regulated behavior to non-regulated behavior (deregulated) and, finally, to dysregulated behavior.